Smart cities: Blockchain, AI, and advanced computing - Sharma, Bhisham; Gupta, Manik; Jeon, Gwanggil (My University, 2024)
This book aims to provide a comprehensive overview of the various services that are available to help cities develop their smart communities. It includes a variety of topics such as artificial intelligence, blockchain, advanced computing, and the Internet of Everything. Smart Cities: Blockchain, AI, and Advanced Computing is structured with independent chapters, each highlighting the current and future state-of-the-art technologies addressing smart city challenges. The book covers a variety of application areas, including healthcare, transportation, smart grids, supply chain management, and financial systems. There are both theoretical and empirical investigations in this book; they cover a wide range of topics related to smart city development and implementation, among others, all of which have a significant impact on the creation of smart cities. This book then examines the state-of-the-art blockchain technology for smart city challenges and programs that might enhance the quality of life in urban areas and encourage cultural and economic growth. This book is written especially for the students, researchers, academicians, and industry professionals looking for initiatives and advancements in technologies with a primary focus on their implications for smart cities.